Avaliação ultraestrutural, dimensional e mecânica de dois sistemas de fixação interna rígida de 2mm - Rocha Junior, Hernando Valentim da (2009)
Introduction: Since the first records that we have treatment for facial fractures, it was noted in the history of mankind a continuous process and always evolving to improve both the technique as the technology used to improve results in the treatment. Today the technique of choice for preferential treatment of facial fractures is the rigid internal fixation with plates and screws up the basis of titanium. Such devices are subject to a number of mechanical applications, after their deployment, which should bear with the highest resistance while maintaining certain flexibility in order to effect its conformation and adaptation during the deployment. This paper aims to compare the two materials used in rigid internal fixation surgery Bucomaxilofacial, from a microscopic, dimensional and mechanical. Material and method: We used three samples of the system boards 2.0mm of each company and is a national company and one imported. The samples were evaluated by SEM and EDS for assessment and identification of surface contaminants. After this analysis all samples submitted to a series of measurements in six different regions. Finally the samples subjected to a test of bending in four points. Results: As a result of the examination by SEM and EDS, we noticed the presence of contaminants, staining, and burrs. In dimensional analysis, had a degree of variability in measures between the plates. Bending to the test can be observed some discrepancy between samples. Conclusion: We observed that the scanning electron microscopy and EDS, the composition of both boards was commercially pure titanium but with some changes in the surface. The dimensional analysis showed a better standardization of imported on the national boards, as well as mechanical testing.